Co-Rumination and Depression in Women: Psychometric Properties of the Co-Rumination Questionnaire - Tanhaye Reshvanloo, Farhad; Torkamani, Marzie; Mirshahi, Sara; Hajibakloo, Nafiseh (International Journal of Education and Cognitive Sciences, 2022)
Co-rumination is characterized by rehashing the problem or parts of the problem, speculating about the causes and consequences of the problem, focusing on negative affect that results from the problem, and mutual encouragement of problem talk. Co-rumination has been shown to be more common and impactful in female friendships’ as compared to males’. The purpose of the present study was to investigate the psychometric properties of the Co-rumination questionnaire in women. In a correlational design, 119 women who referred to health care centers of Mashhad city were selected with the convenience sampling. Data were collected by Co-rumination Questionnaire (CRQ), and Depression, Anxiety and Stress Scale (DASS 21). Confirmatory factor analysis, convergent validity and internal compatibility with SPSS.25 and SmartPLS.3.3.0 software were evaluated. The results showed that the questionnaire has three factors. This structure has a good fit. Cronbach's alpha coefficients ranged from 0.86 to 0.95 and Spearman-Brown’s split-half coefficients ranged from 0.90 to 0.95, indicating good reliability of the questionnaire. Co-rumination had a positive and significant relationship with depression and could predict it. It seems that the Co-rumination Questionnaire has proper validity and reliability and can be used by researchers to predict depression in women.